ROSSLOPE: Past and present sedimentary dynamic in the ROSS Sea: a multidisciplinary approach to study the continental SLOPE - Colizza, E; Bohm, G; Capotondi, L; Finocchiaro, F; Giglio, F; Kuhn, G; Presti, M.; MAFFIOLI, PAOLA; MALINVERNO, ELISA (country:GB, 2011)
The ROSSLOPE is an Italian Antarctic project approved in the framework of the PNRA. The investigation of the interactions among marine currents, sea floor morphology, sediment texture and benthic communities is crucial to understand the dynamics of depositional and erosive processes on present-day seafloor, and represents an important key to study the paleo-environmental variation of the southern antarctic and subantarctic areas. This project aims to investigate the relation between present and past water mass circulation from modern and late-Cenozoic sedimentary sequences of the Ross Sea outer shelf and continental slope of the area of Adare and Central Basins, and the area to the east of Pennell-Iselin Banks. The study will be performed through the comparison and integration of data concerning the circulation of the present dense, cold water masses produced in the Ross Sea (HSSW e ISW), with 1) measurements of physical-chemical-biotic characteristics of surface sediments (water-sediment interface) and within the top 5 meters beneath the seafloor, 2) the geo-morphological features of these areas, 3) benthic acoustic facies typically related both to bottomcurrent activity (i.e. sediment drifts) and to down-slope mass processes within the stratigraphic section. In these areas few and scattered geological, geophysical, oceanographic and morpho-bathymetric data exist. We propose to study these existing data. The data base is constituted of previous data of: 1) multibeam surveys collected during PNRA and USA geophysical cruises 2) single-channel and multichannel Italian and foreign seismic data available by the Seismic Data Library System 3) PNRA sediment box cores and cores of which most already studied for other purposes and others yet to be studied. Moreover new morpho-bathymetric and sub-bottom acoustic data together with cores and box cores will be collected. All results will be compared in a multidisciplinary way with oceanographic knowledge to provide a depositional model of the modern continental slope ...